(untitled) (Proceedings of Southern Federal University. Philology, 2017)
Vladimir I. Karasik (Volgograd, Russian Federation) The article deals with a mythological plot “fratricide” treated as the embodiment of archetypical sin – murder of one’s kin. Associative extension of this crime and its participants is described. Main lines of murderer’s behavior are grudge and uncontrolled fury caused by envy and strife for primacy. Fratricide was repeatedly represented in fiction texts. Various approaches to this plot are analyzed as presented in prose, drama and poetry by S. Gessner, S. Coleridge, G.B. Byron, A. Tarkovsky, R. Shusterovich, G. Kanevsky, A. Barkova, J. Minot, A. Zheleznov. Several vectors of fratricide rethinking are traced including devil’s design, revolt against unjust world order, sacrifice, and incomprehensibility of fate. Metaphorically, this subject plot is exemplified in civil war scripts or in a broader sense in tragic conflict of close friends. Key words: myth, remythologization, subject plot, fratricide, fiction text. DOI 10.23683/1995-0640-2017-3-30-44